Directed Evolution of a Glutathione Transferase for the Development of a Biosensor for Alachlor Determination - Perperopoulou Fereniki; Fragoulaki Maria; Papageorgiou Anastassios C; Labrou Nikolaos E (MDPI, 2022)
In the present work, DNA recombination of three homologous tau class glutathione transferases (GSTUs) allowed the creation of a library of tau class GmGSTUs. The library was activity screened for the identification of glutathione transferase (GST) variants with enhanced catalytic activity towards the herbicide alachlor (2-chloro-2 ',6 '-diethyl-N-(methoxymethyl)acetanilide). One enzyme variant (GmGSTsf) with improved catalytic activity and binding affinity for alachlor was identified and explored for the development of an optical biosensor for alachlor determination. Kinetics analysis and molecular modeling studies revealed a key mutation (Ile69Val) at the subunit interface (helix alpha 3) that appeared to be responsible for the altered catalytic properties. The enzyme was immobilized directly on polyvinylidenefluoride membrane by crosslinking with glutaraldehyde and was placed on the inner surface of a plastic cuvette. The rate of pH changes observed as a result of the enzyme reaction was followed optometrically using a pH indicator. A calibration curve indicated that the linear concentration range for alachlor was 30-300 mu M. The approach used in the present study can provide tools for the generation of novel enzymes for eco-efficient and environment-friendly analytical technologies. In addition, the outcome of this study gives an example for harnessing protein symmetry for enzyme design.